MEK1/2-ERK Pathway Alterations as a Therapeutic Target in Sporadic Alzheimer's Disease: A Study in Senescence-Accelerated OXYS Rats - Natalia A. Muraleva; Nataliya G. Kolosova; Natalia A. Stefanova (MDPI AG, 2021)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder and the most common cause of dementia worldwide, with no cure. There is growing interest in mitogen-activated protein kinases (MAPKs) as possible pathogenesis-related therapeutic targets in AD. Previously, using senescence-accelerated OXYS rats, which simulate key characteristics of the sporadic AD type, we have shown that prolonged treatment with mitochondria-targeted antioxidant plastoquinonyl-decyltriphenylphosphonium (SkQ1) during active progression of AD-like pathology improves the activity of many signaling pathways (SPs) including the p38 MAPK SP. In this study, we continued to investigate the mechanisms behind anti-AD effects of SkQ1 in OXYS rats and focused on hippocampal extracellular regulated kinases' (ERK1 and -2) activity alterations. According to high-throughput RNA sequencing results, SkQ1 eliminated differences in the expression of eight out of nine genes involved in the ERK1/2 SP, compared to untreated control (Wistar) rats. Western blotting and immunofluorescent staining revealed that SkQ1 suppressed ERK1/2 activity via reductions in the phosphorylation of kinases ERK1/2, MEK1, and MEK2. SkQ1 decreased hyperphosphorylation of tau protein, which is present in pathological aggregates in AD. Thus, SkQ1 alleviates AD pathology by suppressing MEK1/2-ERK1/2 SP activity in the OXYS rat hippocampus and may be a promising candidate drug for human AD.